Terminal trajectory of HbA1c for 10 years supports the HbA1c paradox: a longitudinal study using Health and Retirement Study data - Zhang, Zeyi; Yang, Longshan; Cao, Heng (Frontiers in Endocrinology, 2024)
Objectives We aimed to assess the potential time-varying associations between HbA1c and mortality, as well as the terminal trajectory of HbA1c in the elderly to reveal the underlying mechanisms. Design Longitudinal study. Setting and Participants Data were from the Health and Retirement Study. 10408 participants aged ≥50 years with available HbA1c measurements at baseline (2006/2008) were included. Methods Longitudinal HbA1c measured at 2010/2012 and 2014/2016 were collected. HbA1c measured at three times for their associations with all-cause mortality were assessed using Cox regression and restricted cubic splines. HbA1c terminal trajectories over 10 years before death were analyzed using linear mixed-effect models with backward time scale. Results There were 59.6% females, mean age 69 years, with 3070 decedents during the follow-up (8.9 years). The mortality rate during follow-up was 29.5%. Increased mortality risk became insignificant for the highest quartile of HbA1c compared to the third quartile (aHR 1.148, 1.302, and 1.069 for follow-up of 8.9, 6.5, and 3.2 years, respectively) with shorter follow-up, while became stronger for the lowest quartile of HbA1c (aHR 0.986, 1.068, and 1.439 for follow-up of 8.9, 6.5, and 3.2 years, respectively). Accordingly, for both decedents with and without diabetes, an initial increase in HbA1c was followed by an accelerating terminal decline starting 5-6 years before death. Conclusions and Implications The time-varying association between HbA1c and mortality mapped to the terminal trajectory in HbA1c. High and low HbA1c may have different clinical relationships with mortality. The HbA1c paradox may be partially explained by reverse causation, namely early manifestation of death.